Vocational teacher education in five European countries - analysis and comparison - Abele, Stephan [Verfasser]; Norwig, Kerstin [Verfasser]; Nickolaus, Reinhold [Verfasser] (My University, 2009)
"Against the background of the European Commission's endeavour to promote the cooperation between the EU member countries, institutions from five countries involved in VET teacher education have worked together in a project aiming at the development of systems for vocational teacher qualification improvement. The analysis of the current situation of VET teacher education in the different partner countries was taken as the basis for a comparison which as a result allowed developing improvement concepts during the subsequent course of the project. In order to analyse the present situations, a methodology was developed which will be presented along with the analysis and the results of the comparison in this paper. The aspects covered in this analysis furthermore allow a critical discussion on problems that should be considered within the developing process of the European educational systems." (Autorenreferat, BIBB-Doku)
Keywords: P 3.2.3 Lehrer; L 6.2 Qualitätsmanagement/Qualitätssicherung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; Bildungspersonal; Berufsschullehrer; Lehrerausbildung; Kompetenzorientierung; Qualitätssicherung; Internationaler Vergleich; Bundesrepublik Deutschland; Finnland; Italien; Litauen; Rumänien